PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP EFEKVITAS KERJA KARYAWAN DI PT. VINDIA AGRO INDUSTRI KABUPATEN SIMALUNGUN SUMATERA UTARA - Girsang, Santy Yulfiani; Ningsih, Dewita Suryati; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research aims to determine the influence of variable competencies and organizational culture on effectiveness in PT . Vindia Agro Industri Kabupaten Simalungun Sumatra Utara . There is no benefit in giving advice to the leadership of the company PT . VAI and HR managers to be able to increase the effectiveness of employees in order to achieve company goals .The population in this study were 132 employees working at the Sweet Poteto with research samples totaling 52 employees at PT. Vindia Agro Industries. The sampling technique used is the probability sampling random sampling. Methods of data collection in this study is a questionnaire survey using instruments that are delivered directly to the PT. Vindia Simelungun Agro Industrial District of North Sumatra. The method of analysis that is performed multiple regression analysis using the computer program SPSS (Statistical and Service Solutions) version 21.0.Results of research conducted found that the competence and organizational culture variables simultaneously and significant influence on the effectiveness of employees.Based on the research results suggested for the company to pay attention to employee competence, especially on indicators of the ability to manage tasks, the ability to take swift action and the ability to carry out tasks and organizational culture within the company so as to increase the effectiveness of employees in the company in order to achieve a more optimal.Keywords : Effectiveness of the work , Competence and Organizational culture